Product catalog web interface and API - Arnbjörg Bára Frímannsdóttir 1996-; Helga Eyþórsdóttir 1997-; Katrín Ósk Hafsteinsdóttir 1981- (2020)
This report is a part of a final project in BSc and Diploma in Computer Science at Reykjavík University. The project is in collaboration with Vodafone in Iceland and revolves around Vodafone’s Product Catalog system. Product Catalog is an important system for the company, it keeps track of the available product range, discounts, prices and definitions of how products are activated in various systems. The task the team solved was to rewrite the existing Product Catalog web API with modern technology, to facilitate maintenance and additions of new functionality. As well as rewrite the web interface, in order to combine two different interfaces that were in use for the Product Catalog system to improve the use of the system by making all functionality accessible in one interface.